(untitled) (Journal of Laboratory Animal Science, 2019)
The pathomorphological evaluation of antidiabetic effect of hydroalcoholic extract of Momardica charantia (M. charantia) plant’s fruit pulp was studied in streptozotocin (STZ) induced diabetes in Wistar albino rats against glibenclamide. Hydroalcoholic extract of M. charantia at 200 mg/kg was administered to the diabetic subjects for 45 days. The antidiabetic effect was evaluated by estimation of serum glucose, cholesterol, triglyceride, ALT, AST and serum insulin. Detailed histopathologic evaluation of islets of Langerhans, liver and other organs was performed to assess its pathomorphological effects. The diabetic rats which received the hydroalcoholic extract of the M. charantia fruit pulp showed significant decrease (P≤0.001) in the serum levels of glucose, cholesterol, triglyceride, ALT and AST and the serum insulin was significantly increased (P≤0.001) compared to diabetic control animals. The effect observed was almost comparable to those of glibenclamide. The microscopic evaluation of islets of Langerhans indicated either the regeneration or repair of the affected beta cells and also the extract found to have marked hepatoprotective effect against STZ induced liver injury